Sensing DNA opening in transcription using quenchable Forster resonance energy transfer. - Cordes, T; Santoso, Y; Tomescu, A; Gryte, K; Hwang, L; Camará, B; Wigneshweraraj, S; Kapanidis, A (2010)
Many biological processes, such as gene transcription and replication, involve opening and closing of short regions of double-stranded DNA (dsDNA). Few techniques, however, can study these processes in real time or at the single-molecule level. Here, we present a Förster resonance energy transfer (FRET) assay that monitors the state of DNA (double- vs single-stranded) at a specific region within a DNA fragment, at both the ensemble level and the single-molecule level. The assay utilizes two closely spaced fluorophores: a FRET donor fluorophore (Cy3B) on the first DNA strand and a FRET acceptor fluorophore (ATTO647N) on the complementary strand. Because our assay is based on quenching and dequenching FRET processes, i.e., the presence or absence of contact-induced fluorescence quenching, we have named it a "quenchable FRET" assay or "quFRET". Using lac promoter DNA fragments, quFRET allowed us to sense transcription bubble expansion and compaction during abortive initiation by bacterial RNA polymerase. We also used quFRET to confirm the mode of action of gp2 (a phage-encoded protein that acts as a potent inhibitor of Escherichia coli transcription) and rifampicin (an antibiotic that blocks transcription initiation). Our results demonstrate that quFRET should find numerous applications in many processes involving DNA opening and closing, as well as in the development of new antibacterial therapies involving transcription.